Effect of nitrogen and sulphur nutrition on growth, yield and quality parameters in linseed (Linum usitatissimum) varieties: Effect of nitrogen and sulphur nutrition on growth, yield and quality parameters in linseed (Linum usitatissimum) varieties - A V PAWAR; A M MISAL; M R RATHOD; P R THOMBRE (Journal of Oilseeds Research, 2023)
The experiment was conducted with eighteen treatment combinations consisting of two varieties viz. LSL93 (V1) and NL-260 (V2), three levels of N (0,40,60 kg/ha), three levels of S (0,25,50 kg/ha) replicated twice. The results indicated that the growth and yield attributing characters like number of branches, number of capsules, number of seeds/capsule, seed yield, oil content were appreciably better in the variety LSL-93 than NL-260. The application of N@ 60kg/ha and S@ 50kg/ha showed better results in improving the growth and productivity of linseed. Among the treatment combinations, V1N3S3 (LSL-93:N60:S50) was found to be the most effective treatment.